PROSES BERPIKIR SISWA TUNAGRAHITA RINGAN DALAM MEMAHAMI KONSEP SEGITIGA BERDASARKAN TEORI VAN HIELE - Eka, Rizqi; Susanto, Susanto; Setiawani, Susi (Kadikma, 2015)
Abstract. This research describes about thinking process of students with light intellectualdisabilities in understanding concept of triangle. The thinking of students with light intellectualdisabilities based on the Piaget's stage that is disequilibrium, assimilation, accommodation andequilibrium. The description of the thinking of students with light intellectual disabilities will beassociated with the Van Hiele theory. The instrument used in this research was question tests aboutconcept of triangle and guidance interview to dig thinking process of students with light intellectualdisabilities in understanding concept of triangle. When students are confuse or imbalance whengiven test item is called disequilibrium. Stages assimilation occurs when students acquire newknowledge, then if the students are already familiar with the new knowledge will be accommodation.If assimilation and accommodation there will be a balanced is called equilibrium. The resultsshowed that student can mention the character of triangle so well that the student are at level 1(analysis) Van Hiele theory. The other student can also mention the character of triangle, but thecharacter of the vertex of a triangle can not be mentioned so well, therefore that student is at thelevel 0 (visualization) Van Hiele theory.Keywords: Piaget's Stage, Theory Van Hiele, Thinking Process, Students with Light IntellectualDisabilities